Construção de sequência didática com crianças da educação infantil como ferramenta para a formação de percepção botânica - Apolari, Ana Paula (Universidade Federal de São Carlos, 2024)
This dissertation investigates how the approach of Didactic Sequence (DS), based on Delizoicov's Three Pedagogical Moments (TPM) and Paulo Freire's concept of dialogicality, can enhance the understanding of botanical concepts in Early Childhood Education (ECE). The central research question is: how can the implementation of a DS, structured according to TPM and guided by dialogicality, contribute to the construction of botanical knowledge among young children? The methodology adopted is qualitative, utilizing an action-research approach. The study was conducted in a Jardim II class at a municipal school, where a DS specifically designed to introduce botanical concepts in an accessible and engaging manner was applied. The proposed activities included image observation, thematic songs, exploration of the school’s natural environment, and practical activities that encouraged children to recognize and name parts of plants. The primary objective of the research is to evaluate the effectiveness of the DS in promoting the learning of botanical concepts among children in the ECE age group, as well as integrating science into the children's daily lives in a way that stimulates curiosity and active involvement. The research also seeks to understand how TPM can be articulated in pedagogical practice to favor the construction of scientific knowledge from early childhood. The results indicate that the application of the DS, grounded in TPM, resulted in a greater understanding and engagement of the children with botanical content. The children were able to relate the knowledge acquired to their daily lives, demonstrating significant learning. Additionally, the research highlighted the importance of constant dialogue between teacher and students, promoting a learning environment where the children's spontaneous conceptions are valued and pedagogically developed. However, the research also revealed challenges, such as the need for more robust teacher training in the field of Botany, indicating that many professionals still feel insecure when addressing this content in Early Childhood Education.
Developing a Didactic Sequence with Preschool Children as a Tool for Building Botanical Awareness
Keywords: Educação infantil; Sequência didática; Botânica; Atuação infantil; Early childhood education; Didactic sequence; Botany; Child involvement; CIENCIAS BIOLOGICAS::BOTANICA; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM